CITIZENS ’PERCEPTION OF THE ADEQUACY OF THE INSTITUTIONS’ ACTIVITIES IN TERMS OF MENTAL HEALTH PROTECTION REGARDING CLIMATE CHANGES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
Studies have shown that, people suffer from the effects of climate change. Theconsequences of natural disasters include shock reactions, post-traumatic stress disorder(PTSD), depression, anxiety, phobic disordersand suicidal behavior. In addition to poorharvests and economic losses, changes in the natural environment cause a grief and sorrowdue to the loss of important places and landscapes.Every human being is affected by theconsequences of climate change, especially since climate change is at a stage when a “redcode” for humanity is included. Some categories of people are more vulnerable to the potentialimpacts of climate change. They are: children, elderly, chronically ill, people with cognitiveimpairments, limited mobility, pregnant women, people with mental health disorders, withlower socioeconomic status, migrants, refugees, the homeless.In Macedonia in 2021 a surveywas conducted on the impact of the effects of climate change on mental health. Data showedthat although most respondents know what climate change is and consider it a moderate riskin society, almost all respondents said that they cause some of the negative emotions suchas depression, despair, hopelessness, fear and powerlessness. Most of the respondents eitherdo not know what the relevant Macedonian institutions are doing to prevent and mitigatethe consequences of climate change or they think that the Macedonian society is not takingmeasures in that direction.Given the importance of preventing the mental health of thepopulation, we hope that the findings of this research would be useful in creating state policiesand strategies for tackling climate change.